Is there a relationship between juvenile idiopathic arthritis and periodontitis? - Stefan Reichert (journal of clinical periodontology, 2006)
Aim: The aim was to compare the prevalence of periodontal conditions in patients with juvenile idiopathic arthritis (JIA) (n578, age 14.4 years) with those revealed in a healthy control group (n575, age 15.5 years). Material and Methods: In both groups, the approximal plaque index (API), the modified sulcular bleeding index (SBI), and the clinical attachment loss (CAL) were determined. Laboratory parameters for JIA activity included the capsule-reactive protein (CRP) and the immunoglobulins A, G, M. Results: JIA patients had a significantly higher API (64.6% versus 49.9%, p50.004) and slightly higher mean percentages of sites with CAL43.5mm (0.58% versus 0.22%, p50.041). There was no significant difference in the prevalence of patients and controls who had sites with CAL43.5mm (25.6% versus 17.3%, p50.212). The mean CAL was slightly greater (0.2 mm; p50.030) in patients with CRPX5.0 mg/l compared with patients with CRPo5.0 mg/l. Patients who took non-steroidal antiinflammatory drugs (NSAIDs) had a significantly decreased SBI (26.2% versus 51.1%, p50.019). Conclusion: After adjustment for microbial plaque, JIA is not a risk factor for periodontitis.